Learning environment, mathematics achievement and student attitudes among university computing students in Indonesia - Margianti, Eko Sri (Curtin University, 2001)
This thesis reports the findings of a study of the influence of the classroom learning environment on students cognitive and affective outcomes among 2,498 third-year computing students in 50 university-level classes in Indonesia. Students perceptions of the classroom environment were measured using a modified Indonesian version of the What Is Happening In This Class? (WIHIC) questionnaire. To assess students affective outcomes, a scale derived from the Test of Science Related Attitudes was adapted for use in higher education computing classes and translated into Indonesian. Students' final scores in their mathematics course (either linear algebra or statistics) were used as a measure of cognitive achievement. Secondary aims of the present study were to examine whether differences exist between (a) students perceptions of the actual and preferred classroom learning environment, (b) the perceptions of male and female of the actual and preferred classroom environment and (c) students' perceptions of the actual learning environment in linear algebra and statistics courses. The results of this study make important contributions towards explaining why Indonesian students are achieving at less than desirable levels in their computing courses.